(3GdCSO hGdZhGUs
(3ChdgG (B:s
(3CYde Cf GdMceGA LYdJ GdMceI aj Vef GdCNHGQ hYdi CdSf GdMjhGfGJ, haj CKfGA GdMcGjGJ dJNa Ydi GdbdhH, hJgT EdjgG GdCSeGY s
(3BNQgG (B:s
(3Ke EfbWY Edi HjJ ef HjhJ GdYHGOI aj HYV GdLHGd hcGf Gdedc jRhQg Edi Cf aQb GdOgQ HjfgeG Je cJGH GdCSO hGdZhGU HMeO Gddg hefg s
(3hgPg GdfSNI Yf fSNI CNQi ocJHJ SfI (B530(3g`s
(3jdjgG bUjOI ddabjg GdTjYj GdMSjf Hf eMeO Hf Ydj GdeShQjs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B25 s
Keywords: (3GdCOHs